Rounding-up in reported EPS, behavioral thresholds, and earnings management - Das, Somnath (2013)
Reported earnings per share (EPS) are frequently rounded to the nearest cent. This paper provides evidence that firms manipulate earnings so that they can round-up and report one more cent of EPS. Specifically, we examine the digit immediately right of the decimal in the calculated EPS number expressed in cents. Evidence is presented that firms are more likely to round-up when managers ex ante expect rounding-up to meet analysts’ forecasts, report positive profits, or sustain recent performance. Further investigation provides evidence that working capital accruals are used to round-up EPS.